Scaling out sweetpotato and potato-led interventions to improve nutrition and food security in Tigray and SNNPR, Ethiopia - Jogo, W.; Teshome, F. (International Potato Center, 2015)
This flyer is a brief of the ‘Scaling out sweetpotato and potato-led interventions to improve nutrition and food security in Tigray and SNNPR’ project, which is being implemented in the Southern Nations, Nationalities and Peoples’ Region (SNNPR) and the Tigray region in the north of Ethiopia. At present, the project covers a total of 75 kebeles (villages) in 20 woredas (districts) in the two regions. It summarizes the objectives, achievements and lessons of the project between June 2014 and July 2015.